Systematic review and meta-analysis of high-pressure intermittent limb compression for the treatment of intermittent claudication - Oresanya, Lawrence; Mazzei, Michael; Bashir, Riyaz; Farooqui, Aisha; Athappan, Ganesh; Roth, Stephanie; Choi, Eric T.; van Bemmelen, Paul (Journal of vascular surgery, 2018)
High-pressure intermittent limb compression (HPILC) has been proposed as an alternative treatment of disabling intermittent claudication. The objective of this study was to conduct a systematic review and meta-analysis of randomized controlled trials evaluating the efficacy of HPILC in improving walking distance in patients with intermittent claudication. A search through December 31, 2016, was performed to identify all randomized controlled trials evaluating the efficacy of HPILC for the management of intermittent claudication. Applicable studies were assessed for quality and pooled using Cochrane systematic review guidelines. The primary outcome measured was absolute claudication distance (ACD). A random-effects model was used for meta-analysis. Eight studies eligible for inclusion were identified. These studies had a combined total of 290 subjects, 172 of whom were randomized to HPILC. All studies identified an increase in walking distance for subjects receiving compression therapy. On meta-analysis, the mean difference of ACD from baseline to follow-up among subjects receiving compression compared with controls was 125 m (95% confidence interval, 58.38-191.63 m; P < .01). HPILC is associated with a significant increase in ACD compared with controls. Limb compression appears to be an effective, noninvasive treatment option for patients with intermittent claudication. However, there are few studies comparing limb compression with other commonly used therapies. Further studies are needed to better guide the use of HPILC in the treatment of claudication.